High-Precision Nonenzymatic Electrochemical Glucose Sensing Based on CNTs/CuO Nanocomposite - Mithra Geetha (14151807) (2022)
The measurement of blood glucose levels is essential for diagnosing and managing diabetes. Enzymatic and nonenzymatic approaches using electrochemical biosensors are used to measure serum or plasma glucose accurately. Current research aims to develop and improve noninvasive methods of detecting glucose in sweat that are accurate, sensitive, and stable. The carbon nanotube (CNT)-copper oxide (CuO) nanocomposite (NC) improved direct electron transport to the electrode surface in this study. The complex precipitation method was used to make this NC. X-ray diffraction (XRD) and scanning electron microscopy were used to investigate the crystal structure and morphology of the prepared catalyst. Using cyclic voltammetry and amperometry, the electrocatalytic activity of the as-prepared catalyst was evaluated. The electrocatalytic activity in artificial sweat solution was examined at various scan rates and at various glucose concentrations. The detection limit of the CNT-CuO NC catalyst was 3.90 µM, with a sensitivity of 15.3 mA cm−2 µM−1 in a linear range of 5–100 µM. Furthermore, this NC demonstrated a high degree of selectivity for various bio-compounds found in sweat, with no interfering cross-reactions from these species. The CNT-CuO NC, as produced, has good sensitivity, rapid reaction time (2 s), and stability, indicating its potential for glucose sensing. Graphical Abstract Other Information Published in: Journal of Electronic Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11664-022-09727-z